Research progress and hotspot analysis of soil microplastics: a bibliometrics-based review - Miao, Jiarui; Huang, Wenhao; Pan, Ruoxi; Zhou, Kai (Frontiers in Environmental Science, 2023)
Microplastics are ubiquitous in soil ecosystems, and they have attracted widespread attention owing to their accumulation, migration and diffusion in soil environments and their negative effects on the environment and human health. However, previous studies on microplastics have predominantly concentrated on aquatic environments, and their presence in soil ecosystems has seldom been studied systematically. This review presents a systematic analysis of the current research on soil microplastics based on the available literature from 2016 to 2023 using CiteSpace.The most influential journals, authors and countries in this field were identified. Keyword co-occurrence analysis was performed to determine research hotspots, and cluster analysis was employed to provide an accurate summary of this field. Furthermore, burst detection was used to explore research fronts. This review reveals the increasing depth and diversity of research on soil microplastics and discusses potential research fronts for future studies in this field.